(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2023)
Indebtedness is considered one of the most important problems facing Arab countries, due to its negative dimensions on the process of economic development in these countries and its threat to the stability of their financial system. which prompted these countries to borrow, which constituted a huge burden on the borrowing Arab countries in paying the installments agreed upon by the creditor and the interest arising from these loans, and of course, these burdens that are paid are at the expense of the basic services provided by these countries to their citizens, which It leaves negative effects on social and political conditions, in addition to stifling economic growth rates. This research aims to shed light on the factors that played an important role in exacerbating the external indebtedness crisis of Arab countries, and to identify ways that can mitigate the impact of external indebtedness at the local level. Arab and international